Submesoscale Eddy Contribution to Ocean Vertical Heat Flux Diagnosed From Airborne Observations - Hector S. Torres; Alexander Wineteer; Ernesto Rodriguez; Patrice Klein; Andrew F. Thompson; Dragana Perkovic‐Martin; Jeroen Molemaker; Delphine Hypolite; Jörn Callies; J. Thomas Farrar; Eric D’Asaro; Mara A. Freilich (Geophysical Research Letters, 2025)
Abstract Submesoscale eddies (those smaller than 50 km) are ubiquitous throughout the ocean, as revealed by satellite infrared images. Diagnosing their impact on ocean energetics from observations remains a challenge. This study analyzes a turbulent field of submesoscale eddies using airborne observations of surface currents and sea surface temperature, with high spatial resolution, collected during the S‐MODE experiment in October 2022. Assuming surface current divergence and temperature are homogeneous down to 30 m depth, we show that more than 80% of the upward vertical heat fluxes, reaching ∼227 W m−2, is explained by the smallest resolved eddies, with a size smaller than 15 km. This result emphasizes the contribution of small‐scale eddies, poorly represented in numerical models, to the ocean heat budget and, therefore, to the climate system.